EFFICACY AND SAFETY OF INTRA CAESAREAN IUCD - MUZAFFAR , A; PARVEEN , S; ANDLEEB , G; IQBAL , A (Biological and Clinical Sciences Research Journal, 2023)
The objective of this study was to evaluate the effectiveness and complications of post-partum intrauterine contraceptive device (PPIUCD) insertion during cesarean delivery. The study was conducted at Nishtar Medical Hospital from June to December 2022. A total of 150 women were included in the study. In the first phase, medical eligibility for the intervention was assessed, while in the second phase, WHO Medical Eligibility Criteria were evaluated. The IUCD was manually inserted after delivery with its string towards the cervix. The patients were followed up at 2 and 6 months. After 6 months, 9 (6%) cases reported abdominal pain, 22 (15%) had menorrhagia, and 23 (15.3%) had missed threads with the IUCD in place. None of the patients reported pregnancy or perforation of the uterus. After 6 months, 133 (88.6%) patients continued to use this method of contraception, while 9(6%) were lost to follow-up, 4 (2.6%) had the device removed due to complications, and 4 (2.6%) had spontaneous expulsion. The study concluded that PPIUCD is a safe and effective long-term contraceptive method. Clinicians should evaluate patients’ eligibility for PPIUCD and counsel women on adopting this method.